The genome sequence of the Brown House-moth, Hofmannophila pseudospretella (Stainton, 1849) - Boyes, D; Holland, PWH (F1000 Research Ltd, 2023)
We present a genome assembly from an individual male Hofmannophila pseudospretella (the Brown House-moth; Arthropoda; Insecta; Lepidoptera; Oecophoridae). The genome sequence is 406.2 megabases in span. Most of the assembly is scaffolded into 28 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled and is 15.5 kilobases in length.